PENGUJIAN ANGKA LEMPENG TOTAL PADA PRODUK KOSMETIK DI BALAI PENGAWAS OBAT DAN MAKANAN DI KUPANG - Malfiona Ivanka Ledoh; Maya F. Roman; Abdonia W. Finmeta; Nur Aini Bunyani; Fadhila Putri Imananta (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
Cosmetics are materials or preparations intended for use on the external parts of the human body such as the epidermis, hair, nails, lips, and external genital organs, or teeth and oral mucous membranes, primarily to cleanse, perfume, change appearance, and/or improve body odor or protect or maintain the body in good condition. Contamination is something that enters cosmetics unintentionally and cannot be avoided, originating from processing, storage, and/or raw materials. This research aims to determine the level of microbial contamination and hygiene in cosmetic products, measure the total aerobic microbial colony count grown on a specific culture medium in cosmetic preparations, and ensure that cosmetic products are safe to use and meet established health safety standards. The method used in the Total Plate Count Test for Cosmetics according to MA PPOMN is the pour plate method. The test results show that the number of bacterial colonies in all samples is below the maximum limit of microbial contamination set by BPOM, which is 1x10 CFU/g. Sample K.004 has 5 CFU/g, K.012 and K.016 each have 10 CFU/g, S.001 has 15 CFU/g, and M.002 has 25 CFU/g. All research results indicate that the cosmetic product ingredients are still within safe limits for use.